TURN-TAKING PATTERNS AND THE FUNCTIONS OF OVERLAPS IN CONVERSATIONS - Amanat, Luthfi Rahinal (2015)
The present study investigates turn-taking patterns and the functions of overlaps in The Young Turks TV interview Program. Data were taken from 32 minutes of recorded interview between two participants in Special Interview with Larry King. Data were analyzed qualitatively supported by descriptive quantification using turn-taking theory from Sack et al and overlap theory from Adda et al (2008). The study has found that there were three patterns of turn-taking occurred in this study based on turn-taking rules, i.e. CS2TNS (28,13%), SS (64,93%), and CSC (6,94%). There were also overlaps that occurred in the conversations that can be categorized into Backchannel (24,66%), Anticipated Turn-taking (15,07%), Complementary (23,29%), and Turn-stealing (36,99%). Based on the setting of conversation, the functions of overlaps were applied generally to pursue the topic, agree or disagree, emphasize, clarify, and opening or closing the interview. It is concluded thatthe patterns of turn-taking and overlap made a better flow to the TV program and made the interview more interesting to the audiences. Keywords:Conversation Analysis, Turn-taking, Overlap, TV interview Penelitian ini menginvestigasi pola turn-taking dan fungsi dari overlap di program TV The Young Turks. Data diambil dari rekaman interview selama 32 menit antara 2 partisipan di interview spesial bersama Larry King. Data dianalisa secara kualitatif dan didukung oleh deskripsi menggunakan teori turn-taking Sack et al dan teori overlap dari Adda et al (2008). Penelitian ini menemukan bahwa ada tiga pola turn-taking terjadi di dalam penelitian ini yang berdasar kepada aturan turn-taking, yaitu: CS2TNS (28,13%), SS (64,93%), dan CSC (6,94%). Terdapat juga overlap yang terjadi di dalam percakapan yang dapat dikategorisasikan menjadi Backchannel (24,66%), Anticipated Turn-taking (15,07%), Complementary (23,29%), danTurn-stealing (36,99%). Berdasarkan kepada latar percakapan, fungsi dari overlap secara umum adalah untuk mengejar topik, setuju atau tidak, menekankan, mengklarifikasi, dan membuka atau menutup interview. Kesimpulannya, pola turn-takingdan overlap membuat alur percakapan di program TV menjadi lebih baik dan membuat interview menjadi lebih menarik untuk ditonton oleh pemirsa. Keywords:Conversation Analysis, Turn-taking, Overlap, TV interview